DIFFERENTIAL EFFECTS OF THE TRANSIENT OUTWARD K(+) CURRENT ACTIVATOR NS5806 IN THE CANINE LEFT VENTRICLE - Calloe, Kirstine (2009)
OBJECTIVE: To examine the electrophysiological and molecular properties of the transient outward current (I(to)) in canine left ventricle using a novel I(to) activator, NS5806. METHODS AND RESULTS: I(to) was measured in isolated epicardial (Epi), midmyocardial (Mid) and endocardial (Endo) cells using whole-cell patch-clamp techniques. NS5806 activation of K(v)4.3 current was also studied in CHO-K1 cells and Xenopus laevis oocytes. In CHO-K1 cells co-transfected with K(v)4.3 and KChIP2, NS5806 (10 μM) caused a 35 % increase in current amplitude and a marked slowing of current decay with τ increasing from 7.0±0.4 to 10.2±0.3 ms. In the absence of KChIP2, current decay was unaffected by NS5806. In ventricular myocytes, NS5806 increased I(to) density by 80%, 82%, and 16% in Epi, Mid, and Endo myocytes, respectively (at +40 mV) and shifted steady-state inactivation to negative potentials. NS5806 also significantly slowed decay of I(to), increasing total charge to 227%, 192% and 83% of control in Epi, Mid and Endo cells, respectively (+40 mV, p<0.05). Quantification of K(v)4.3 and KChIP2 mRNA in the 3 ventricular cell types revealed that levels of K(v)4.3 message was uniform but those of KChIP2 were significantly greater in Epi and Mid cells. The KChIP2 gradient was confirmed at the protein level by Western blot. CONCLUSIONS: Our results suggest that NS5806 augments I(to) by increasing current density and slowing decay and that both depend on the presence of KChIP2. I(to) and its augmentation by NS5806 are greatest in Epi and Mid cells because KChIP2 levels are highest in these cell types.